2016
DOI: 10.18074/cnuiibf.318
|View full text |Cite
|
Sign up to set email alerts
|

Türkiye'de Kredi Genişlemesinin Cari Açığa Etkisi: Sınır Testi Yaklaşımı

Abstract: Bu çalışmada, hem siyasi hem ekonomi otoritelerince son zamanlarda sıkça ifade edilen, "Türkiye'de yurtiçi toplam kredi hacmi artışının cari açığın artışı üzerinde büyük bir baskıya neden olduğu" iddiası araştırılmaktadır. Ekonometrik analiz için, 1992Q1-2014Q3 dönemi üç aylık kredi hacminin GSYH' ya oranı ve cari açığın GSYH 'ya oranı verileri kullanılmıştır. Bu seriler arasındaki nedensellik ilişkisi için Toda-Yamamoto (1995) ve Dolado-Lütkepohl (1996) nedensellik testleri kullanılırken, eşbütünleşme için is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(1 citation statement)
references
References 5 publications
0
1
0
Order By: Relevance
“…As a result of the regression analysis, there is a positive relationship between bank loans and current account deficit. Also, Motonishi and Yoshikawa (1999), Kunieda and Shibata (2005), Biztis and others (2008), Telatar (2011), Göçer andothers (2013), , Morel Benito and Roehn (2016), Dücan and others (2016), Davis and others (2016) and Akçayır and Albeni (2016) reached equivalent results in their studies. On the contrary, Begeç (2015) concluded that loan amount does not have any effect on current account deficit by using Johansen co-integration analysis.…”
Section: Literature Reviewmentioning
confidence: 78%
“…As a result of the regression analysis, there is a positive relationship between bank loans and current account deficit. Also, Motonishi and Yoshikawa (1999), Kunieda and Shibata (2005), Biztis and others (2008), Telatar (2011), Göçer andothers (2013), , Morel Benito and Roehn (2016), Dücan and others (2016), Davis and others (2016) and Akçayır and Albeni (2016) reached equivalent results in their studies. On the contrary, Begeç (2015) concluded that loan amount does not have any effect on current account deficit by using Johansen co-integration analysis.…”
Section: Literature Reviewmentioning
confidence: 78%